PERLINDUNGAN HUKUM BAGI PEMEGANG HAK MEREK DI INDONESIA - I MADE DIYAMA PUTRA; TITIN TITAWATI; ALINE FEBRIYANI L; GDE TUSAN ARDIKA (Universitas Mahasaraswati K. Mataram, 2022)
This study aims to examine and analyze how legal protection and legal remedies can be carried out by trademark rights holders who feel aggrieved. This research uses a form of normative legal research, namely research based on written legislation and various related literature. with the problems that will be discussed in this study.The form of legal protection for trademark rights holders is the existence of Law Number 20 of 2016 concerning Marks and Geographical Indications (UU MIG), and Permenkumham Number 67 of 2016 which regulates trademark registration. harmed is a. Mark rights holders may apply for a written provisional injunction to the Commercial Court, b. Mark rights holders may file a civil lawsuit, in the form of compensation, termination of the use of the violated mark, c. Trademark rights holders can file criminal charges